Pengaruh Penggunaan Metode Pembelajaran, Intellegence Quotient (IQ) dan Kemampuan Berbahasa Terhadap Hasil Belajar - Holisah (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2022)
Learning method is estimated can improve the student’s performance. Besides learning method, the learning outcomes are determined by many factors, there are IQ and language skills. Therefore, this research was intended to know about the influence of learning method, IQ and language skills of senior high school student’s learning outcomes. The research was quantitative by using experimental methods. The population was from all of students grade XI IPA at senior high schools of SMAN 1 Baros. There were 70 students as the sample. The Data analysis techniques on this research used Anava Three Line. The result of the research showed: There was a significant effect on the learning method towards learning outcomes, There was no significant influence of IQ towards learning outcomes, There was no interaction effect on language skills towards learning outcomes, There was no interaction effect on learning methods and IQ towards learning outcomes, There was no interaction effect on learning approach and the language skills towards learning outcomes, There was no interaction between IQ and language skills towards learning outcomes, Simultaneously, there was no interaction effect of learning methods, IQ and language skills towards senior high school students’ learning outcomes.